ANALISIS KANDUNGAN SENYAWA FENOLIK EKSTRAK ALGA Sargassum polycystum DARI PANTAI SELATAN, GUNUNG KIDUL, YOGYAKARTA - Lailatussifa, Radipta -; Pereira, Maria Madalena (Politeknik Kelautan dan Perikanan Sidoarjo, 2022)
Sargassum sp. is one of the abundant brown algae on the South Coast of Yogyakarta. This algae has pharmacological activity in the form of metabolite biological activity, one of which is as an antioxidant. Regarding its ability as an antioxidant, information is needed regarding the polyphenol content in the algae S. polycystum. The aims from this research were to determine of phenolic content analysis of Sargassum polycystum brown algae from South Beach, Gunung Kidul, Yogyakarta quantitatively related to its total phenolic content and qualitatively consisting of Thin Layer Chromatography (TLC) and HPLC (High Performance Liquid Chromatography) tests. Polyphenol was extracted with ethanol 96% and calculated the yield. The yield from fresh algae to powdered algae was 9%, while the yield from fresh algae to ethanolic extract was 5.1%. The value of the total phenolic content extract at a concentration of 1000 ppm was 59.30±0,58 g GAE/100 g dried extract. The TLC test was performed using gallic acid and phloroglucinol standard, while the HPLC test was performed using gallic acid, phloroglucinol and phenol standard. The TLC dan HPLC results showed that ethanolic extract of Sargassum polycystum was suspected to contain polyphenols that resembled of gallic acid and phenol standards.